FAKTOR PENYEBAB KETERLAMBATAN PENGIRIMAN BARANG REGULER DARI GUDANG PUSAT KE CONSIGNEE PADA JASAN COURIER DOMESTIK PT. CARAKA YASA JAKARTA TAHUN 2012 - karno karno (Fakultas Ekonomi Universitas Borobudur, 2015)
This study aims to determine the development of the regular delivery of goods from the central warehouse to the consignee. To determine the factors that cause delays in delivery of goods regulary from the central warehouse to consignee. Determine effective actions.solutions to the root causes major delays in delivery of goods regulary from the central warehouse to the consignee. By using a causakl diagram is a diagram that shows the relationship between cause and effect. The result showed that the development of regular shipments in 2012, on average on average time by 93% and the average delay of 7%. Factors causing delays in deliveri of regular goods is the warehouse area has not been propotional to the amount of goods to be sent, less skilled employees in charge of data items in the system, lack of training and skills of employees.